Interfacial assembly of metal nanoparticles for surface enhanced Raman spectroscopy - Amirah Nur Izzaty Bakram (2019)
Metal nanoparticles possess great optical properties, among many others, and are used in multiple applications. One of the most important application is the enhancement of the Raman scattering signals, which on its own is known to be too weak to be measured. However, surface-enhanced Raman scattering (SERS) often comes from the aggregates of metal nanoparticles that are not homogenous, causing some signals to be strong and others weak. In this project, a method on how to make the SERS signals homogenous is implemented through the fabrication of 2D-assembly of the metal nanoparticles as SERS substrates. Different types of nanoparticles are synthesized from gold seeds, mainly, gold nanorods, gold nano-octahedra, silver-coated nanorods and silver-coated nanocubes. They are first surface-modified by polydopamine (PDA) and then undergo self-assembly at the water-oil interface. After transferred to a glass substrate, the SERS activity was measured with Rhodamine B as the Raman dye. Our results have showed that the self- assembled SERS substrates are able to provide relatively uniform enhancement factors.